PROFESSIONALISM, AVAILABILITY OF TEACHING TRAINEE TEACHERS AND LECTURERS TEACHING PRACTICUM SUPERVISION ADVISORS AT THE INSTITUTE OF TEACHER EDUCATION, SABAH ZONE - Mohamad Nizam Nazarudin; Nur Fatihah Luciana Benjamin Abdullah; Zakiah Noordin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
this study aimed to identify the relationship between professionalism and willingness toteach trainee teachers with teaching Practicum supervision lecturer advisors. This survey using aquestionnaire involving sample 113 respondents from among the teachers of primary school traineeteachers from three other Institute of teacher education in the zone, which is in the practicum phasethree and are in semester 7. The data collected was analyzed descriptively and motivated through theT-test, comparison of mean, one way ANOVA and Pearson Kolerasi also. Analysis of the data foundthat there is no significant difference teaching supervision based on option and the Institute of teachereducation. Pearson Kolerasi analysis did find that there is a significant relationship betweenprofessionalism and willingness to teach the teaching supervision with lecturer advisors.